E-participation for combating corruption, increasing voice and accountability, and developing government effectiveness: A cross-country data analysis - Waheduzzaman, Wahed; Khandaker, Sarod (Australian journal of public administration, 2022)
The national-level data extracted from the World Bank, Transparency International, and the United Nations databases were analysed in this study to examine the contribution of e-participation in improving governance factors through its influence on corruption, voice and accountability, and government effectiveness. The analysis has provided a mixed outcome in improving governance through e-participation, showing a significant relationship between e-participation and corruption perception, and government effectiveness. Meanwhile, the relationships between e-participation and voice and accountability are insignificant. This finding indicates that the present form of e-participation in ensuring citizens' voices for holding service providers accountable may have some limitations. The findings have implications for international organisations and government institutions to redesign their e-participation methods and tools to warrant citizens' voice and ensure accountability of service providers at the national level.